ANALISIS KALIMAT BERDASARKAN POLA KALIMAT DASAR DAN KALKULUS PREDIKAT - Liusti, Siti Ainim (Sunan Kalijaga State Islamic University Yogyakarta, 2016)
This study aims to analyze the sentences based on the basic sentence patterns of Indonesian and predicate calculus. These approaches put the predicate as a core component in the sentence structure. The object of study is focused on declarative sentences of Indonesian. The data analysis consists of several stages. Basic sentence patterns of Indonesian consist of identifying the type of sentences, identifying the elements forming sentences, and putting on elements which are based on basic sentence patterns of Indonesian. Predicate calculus consists of identifying atomic or compound propositions, determining the predicate and other components, defining a form of expression predicate calculus, and making a notation function. The results showed that the basic sentence pattern analysis only identifies the internal elements in a single sentence, while the predicate calculus can as well identifies the internal elements of a single or compound sentence.